Capital Structure and Profitability of Commercial Banks in Nepal (The Mega Journal, 2024)
The study intends to look into how capital structure affects a Nepalese commercial bank's profitability. The statistical analysis of the study includes the secondary data. Using software for analysis, Descriptive and a casual comparative analysis has conducted by gathering data from bank websites and using correlations and multiple regression models for hypothesis testing. Out of the entire population, 12 bank has taken as a sample for the study. The capital structure and profitability have been investigated as a cause and effect relationship using a casual comparative research design. In this study NIM is used as dependent variables, and leverage ratio, bank size, liquidity ratio, and capital ratio are independent variables. As a statistical tool, the following tools are used: mean, standard deviation, correlation, multiple regression model, and hypothesis testing. Excel and SPSS are both used to evaluate those variables. Leverage Ratio has a negative and significant impact with NIM on Nepal's commercial banks. Bank Size has remained negatively and insignificantly impacted with NIM. The Liquidity Ratio shows significantly and positively affects with NIM. The capital ratio has a significant and favorable impact on NIM. However, Banks should value the significance of other variables.